2021
DOI: 10.2147/ceg.s297428
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Disease Outcomes: Does Gastrointestinal Burden Play a Role?

Abstract: Background:The novel coronavirus disease 2019 presents an urgent threat to global health. As the epidemic grows, prognosis prediction is essential for monitoring risky patient. It is thus important to consider gastrointestinal manifestations and the duration of symptoms as predictors of prognosis. Our aim was to determine the correlation of gastrointestinal symptoms and laboratory markers with disease outcomes and whether symptom duration varies substantially between patients. We also undertook this study to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…While three studies by Mao R et al, Wang H et al, and Deane K et al found no significance in the presence of diarrhea and prevalence of severe COVID-19 disease (OR = 1.22, 95% CI: 0.81-1.84; OR = 1.24, 95% CI: 0.90-1.72; OR = 0.82, 95% CI: 0.47-1.44). 1,[9][10][11][12]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…While three studies by Mao R et al, Wang H et al, and Deane K et al found no significance in the presence of diarrhea and prevalence of severe COVID-19 disease (OR = 1.22, 95% CI: 0.81-1.84; OR = 1.24, 95% CI: 0.90-1.72; OR = 0.82, 95% CI: 0.47-1.44). 1,[9][10][11][12]…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study by Hegazy MA et al (2021) found significant factors between the mild and severe cohorts. 10 Where age, sex, presence of chronic lung diseases and metabolic comorbidities were factors that have a significant impact on COVID-19 severity. 10 These factors were then used to adjust the analysis of diarrhea as an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations